Early Christian discourses on Jesus' prayer at Gethsemane : courageous, committed, cowardly? - Sandnes, Karl Olav, 1954- (Novum Testamentum, Supplements, 2016)
From early on, Christians passed down the account of Jesus's agony at the prospect of his own death and his prayer that the cup should pass from him (Gethsemane). Yet, this is a troublesome aspect of Christian tradition. Jesus was committed to his death, but as it approached, he prayed for his escape, even as he submitted himself to God's will. Ancient critics mocked Jesus and his followers for the events at Gethsemane. The 'hero' failed to meet the cultural standards for noble death and masculinity. As such, this story calls for further reflection and interpretation. The present book unfolds discourses from the earliest centuries of Christianity to determine what strategies were developed to come to terms with Gethsemane.